Combined cervical transcutaneous with lumbosacral epidural stimulation improves voluntary control of stepping movements in spinal cord injured individuals - Angeli, Claudia A.; Gerasimenko, Yury (Frontiers in Bioengineering and Biotechnology, 2023)
Lumbosacral spinal cord neuromodulation has shown the ability to restore voluntary control and stepping in individuals with chronic spinal cord injury. We combined cervical transcutaneous and lumbar epidural stimulation to explore the brain-spinal connectomes and their influence in spinal excitability and interlimb coupling. Results showed an inhibition of motor evoked potentials generated by spinal cord epidural stimulation when cervical transcutaneous stimulation is applied. In contrast, when intentional stepping is performed in a non-weight bearing setting, range of motion, motor output amplitude, and coordination are improved when cervical transcutaneous and lumbar epidural stimulations are combined. Similarly, with both stimulations applied, coordination is improved and motor output variability is decreased when intentional stepping is performed on a treadmill with body weight support. Combined transcutaneous cervical and epidural lumbar stimulation demonstrated an improvement of voluntary control of stepping in individuals with chronic motor complete paralysis. The immediate functional improvement promoted by the combination of cervical and lumbar stimulation adds to the body of evidence for increasing spinal excitability and improvement of function that is possible in individuals with chronic paralysis.